The prevalence of chronic dehydration and associated with cardiometabolic risks among agriculture and aquaculture workers - Wang, Ta-Chin; Tsai, Yuan-Hsiung; Yang, Jen-Tsung; Lin, Ming-Shyang; Lin, Yu-Chih; Huang, Tung-Jung; Chen, Mei-Yen (Frontiers in Public Health, 2023)
Background: Chronic dehydration is associated with complications and mortality in acute ischemic stroke patients. Prior literature indicates that farmers and fishery workers are commonly affected by cardiometabolic diseases and there is a need for early prevention of stroke. This study explores the prevalence of dehydration and the association of cardiometabolic risk profiles in agricultural and aquaculture workers.We conducted a community-based, cross-sectional study of agriculture and aquaculture workers in Yunlin County of Taiwan between August 1 and December 31, 2021. Data on demographic characteristics and health-related lifestyles were collected through one-on-one interviews using a questionnaire. The threshold for dehydration is defined as serum osmolality ≥295 mOsm/kg, and physiological biomarkers were collected from a collaborating hospital. Multivariable logistic regression analyses adjusted for demographic characteristics were performed to investigate the association between dehydration levels, cardiometabolic risks, and health-related behaviors.Results: A total of 962 Taiwanese agriculture and aquaculture workers who were predominantly women (65%) with a mean age of 64 years (SD = 13.8) were enrolled.The findings showed a high prevalence of dehydration (36%), metabolic syndrome (44.5%), abnormal waist circumference (64.4%), and abnormal blood pressure (68.5%).Multivariate logistic regression demonstrated that dehydration was significantly associated with metabolic syndrome (p<0.001), 10-year stroke risk prediction (p<0.001), and an unhealthy lifestyle (p<0.001).The prevalence of chronic dehydration was higher in Taiwanese agriculture and aquaculture workers, which was significantly associated with cardiometabolic risks and unhealthy lifestyles.